Clinical Manifestations of Mesoendemic Onchocerciasis in an Area with Multiple Filarial Species - EC Uttah (Iranian Journal of Parasitology, 2009)
"nBackground: The Imo River Basin, Nigeria is endemic for onchocerciasis, bancroftian filariasis, loaiasis and mansonellosis. This study was aimed at determining the clinical manifestations of onchocerciasis in this region. "nMethods: A cross-sectional study was carried out in 2006 in Umuowaibu I and Ndiorji communities in Okigwe Local Government Area of Imo State, Nigeria. Consenting individuals were examined for various gradations of skin manifestations, subcutaneous nodules, and visual impairments by qualified medical doctors. Five categories of skin manifestations were observed, namely permanent itching, onchodermatitis, atrophy of skin, leopard skin, and sowda. A total of 1024 individuals were examined. "nResults: The prevalence of the skin manifestations were permanent itching (2.5%), onchodermatitis (3.9%), atrophy of the skin (5.8%), leopard skin (22.1%), and sowda (0.1%). The prevalence of subcutaneous nodules was 25.3%, but 88.9% among the oldest age group, and mostly found in lower half of body. The majority of cases of visual acuity problems (6.8% overall prevalence) were in the oldest age groups. Among those who were ≥ 20 years old, the prevalence of visual acuity problems was significantly higher in females than in males (χ2-test; P< 0.05). Only two of the examined persons were observed to be blind. "nConclusion: Clinical manifestations of onchocerciasis are perhaps more intense in the area probably because of presence of endemic infections of other filarial species.